TALKING DRAWING STRATEGY IN TEACHING READING COMPREHENSION - Nopa Yuliana (STKIP PGRI Lubuklinggau, 2018)
The objective of this study was conducted to find out whether significantly effective or not to taught reading descriptive text to the seventh grade students of SMP Negeri 7 OKU by using talking drawing strategy. To analyzed the data writer used test as an instrument. The methodology of this study was experimental research and the writer used pre-experimental design. From the population, the writer took class VIIIB as a sample, and the total number of sample was 34. The samples were taken by using cluster random sampling. The students’ mean score in pre-test was 60.47 and students’ mean score in post-test was 73.65. Based on the distribution of students’ score in pre-test and post-test talking drawing strategy was effective to taught reading decriptive text to the seventh grade students of SMP Negeri 7 OKU because the students’ score in post-test was better than pre-test. The minimum score in pre-test was 44 and the maximum score was 80, while the minimum score in post-test was 52 and the maximum score was 92. Based on the the result of the statistical calculated using sample paired t-test found in SPSS 20, it was found that tobtain was 8.804 higher than ttable was 1.699. It means that there were significantly effective to teach reading comprehension to the seventh Grade Students of SMP Negeri 7 OKU by using talking drawing strategy.